A composite metal ceramic material and preparation method thereof

By using Mo-Zr/CNT composite material as the binder and CoB powder as the hard phase in composite cermet materials, combined with specific preparation methods, the problem of poor metal ion dispersion is solved, and ceramic materials with high hardness, high fracture toughness and excellent high temperature performance are achieved.

CN116043089BActive Publication Date: 2025-03-14BAOJI AOHUA CERAMIC TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211702321.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-28
Publication Date
2025-03-14
Estimated Expiration
2042-12-28

AI Technical Summary

Technical Problem

The metal ions in composite cermet materials have poor dispersion in ceramic materials, resulting in lower hardness and fracture strength of ceramic materials.

Method used

Mo-Zr/CNT composite material is used as the binder and CoB powder is combined as the hard phase. Through a specific preparation method, including dissolving Mo(NO3)6·6H2O and ZrCl4 in dimethylformamide, adding 2-methylimidazolium, calcining to obtain Mo-Zr/CNT, then mixing with Ti(C,N) powder and ball milling, and finally sintering in a vacuum hot-pressing sintering furnace.

Benefits of technology

The dispersion of Mo-Zr is improved and its grain size is reduced. The toughening effect of carbon nanotubes improves the density and performance of ceramic materials, and realizes composite metal cermet materials with high hardness, high fracture toughness and excellent high temperature performance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention belongs to the technical field of metal ceramic materials, and specifically relates to a composite metal ceramic material and a preparation method thereof, which solves the problem that the metal ions in the traditional composite metal ceramic materials have poor dispersibility in ceramic materials. The composite metal ceramic material includes a binder and a hard phase, wherein the binder is 10-20 parts of Mo-Zr / CNT composite material, and the hard phase is 80-100 parts of CoB powder. In the technical scheme of the present invention, the MoF material is calcined to obtain a Mo-Zr / CNT composite material, wherein the Mo-Zr is constrained by carbon nanotubes, the dispersion of Mo-Zr is improved and the grain size of Mo-Zr is reduced, the carbon nanotubes have a toughening effect, and the small particles of Mo-Zr enhance the compactness between the carbon nanotubes and ceramics, so the carbon nanotube composite ceramic material is synthesized using Mo-Zr / CNT as a binder, with high density, uniform distribution, high hardness and high fracture toughness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal ceramic materials, and in particular relates to a composite metal ceramic material and a preparation method thereof. Background Art

[0002] Ceramic materials are usually compounds composed of metal and non-metal elements, with ionic bonds and covalent bonds as the main bonding bonds. The performance can be changed by changing the crystal structure. Ceramic materials include glass such as industrial glass; special ceramic materials such as capacitors; metal ceramic materials, etc. Metal ceramic materials usually have higher mechanical strength, which is several times higher than ordinary ceramics; at the same time, metal ceramic materials also have the characteristics of good wear resistance and high hardness; in addition, metal ceramic materials also have the characteristics of good high temperature resistance, good corrosion resistance, and good insulation.

[0003] At present, the metal ions in composite metal ceramic materials have poor dispersion in ceramic materials, resulting in low hardness and fracture strength of the ceramic materials, and greatly reducing their practicality. Summary of the invention

[0004] 1. Technical issues to be resolved

[0005] The purpose of the present invention is to provide a composite metal ceramic material and a preparation method thereof, which solves the problem of poor dispersion of metal ions in the composite metal ceramic material.

[0006] (II) Technical solution

[0007] To solve the above problems, the present invention provides a composite metal ceramic material, including a binder and a hard phase, wherein the binder is 10-20 parts of a Mo-Zr / CNT composite material, and the hard phase is 80-100 parts of a CoB powder.

[0008] A composite metal ceramic material, a method for preparing the Mo-Zr / CNT composite material, comprising the following steps:

[0009] S1, Mo(NO3)6·6H2O and ZrCl4 were dissolved in dimethylformamide, and then 2-methylimidazolium was added to the solution. After stirring at room temperature for 10 min, the reaction mixture was kept at 160 °C in an oven for 24 h, and washed twice with ethanol to obtain Mo-based MOF / ZrO2;

[0010] S2, drying the obtained Mo-based MOF / ZrO2 in an oven at 70°C for 12 h, and then calcining the obtained product at 700°C for 2 h in an argon / hydrogen atmosphere of 95% Ar, 5% H2 to obtain Mo-Zr / CNT;

[0011] S3, the obtained Mo-Zr / CNT and Ti(C,N) powder mixture was fully mixed, and wet mixed in a full planetary ball mill vial equipped with stainless steel balls and ethanol as a medium for 15 h at a speed of 150 r / min, dried at 70 °C and passed through a 100 mesh sieve to obtain a mixed powder;

[0012] S4. Place the obtained mixed powder in a vacuum hot pressing sintering furnace for sintering. The sintering temperature range is 1450-1650°C. The heating rate from room temperature to 800°C is 10°C / min, and the heating rate from 800°C to the sintering temperature is 6.25°C / min. When the temperature reaches 900°C, start to apply biaxial pressure. When the temperature reaches the set maximum temperature, the pressure is simultaneously increased to 34MPa. After maintaining the temperature and pressure for 30 minutes, the sample is cooled in the furnace to obtain the finished product.

[0013] Preferably, in step S1, the mass ratio of Mo(NO3)6·6H2O, ZrCl4, dimethylformamide and 2-methylimidazolium is 400-500:180-220:130-160:3-6.

[0014] Preferably, in step S3, the mass ratio of the Mo-based MOF / ZrO2 and Ti(C, N) powder mixture is 100-300:50-150.

[0015] A method for preparing a composite metal-ceramic material comprises the following steps:

[0016] (1) Weigh the above materials according to the components, put the Mo-Zr / CNT composite material and CoB powder into an omnidirectional planetary ball mill for wet mixing and ball milling for 15 h, the ball mill speed is 150 r / min, the mixing medium is 8 mm and 4 mm diameter stainless steel balls, the ball-to-material ratio is 15:1, and a crude product is obtained;

[0017] (2) The obtained crude product was placed in a vacuum drying oven for drying, then placed in a cylindrical graphite mold, and then placed in a vacuum hot pressing sintering furnace with a vacuum degree of 1×10 -2 Pa-1×10 -3 Pa, first pre-pressing is carried out with a pressure of 7MPa, and then the temperature is gradually raised to 1450℃-1650℃ for pressure sintering, wherein bidirectional pressure is applied at a set temperature range of 1000℃ until the pressure is raised to 34MPa in the insulation stage. After insulation and pressure maintenance for 30min, the finished product is obtained by cooling with the furnace.

[0018] (III) Compared with the prior art, the method of the present invention has the following beneficial effects:

[0019] (1) In the technical scheme of the present invention, Mo(NO3)6·6H2O and ZrCl4 are dissolved in dimethylformamide to obtain MoF material, and the MoF material is calcined to obtain Mo-Zr / CNT composite material, wherein Mo-Zr is constrained by carbon nanotubes, which improves the dispersion of Mo-Zr and reduces the grain size of Mo-Zr. Carbon nanotubes have a toughening effect, and small particles of Mo-Zr enhance the density between carbon nanotubes and ceramics. Therefore, Mo-Zr / CNT is used as a binder to synthesize a carbon nanotube composite ceramic material with high density, uniform distribution, high hardness and fracture toughness.

[0020] (2) The present invention is novel in concept. The CNT-CoB composite metal ceramic material with Mo-Zr / CNT as a binder has the advantages of high purity, high density, uniform distribution, high hardness and fracture toughness, excellent high-temperature performance, simple process, low raw material cost, and easy industrialization. DETAILED DESCRIPTION

[0021] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] Example 1

[0023] A composite metal ceramic material comprises a binder and a hard phase, wherein the binder is 10 parts of a Mo-Zr / CNT composite material and the hard phase is 80 parts of CoB powder.

[0024] The preparation method of Mo-Zr / CNT composite material comprises the following steps:

[0025] S1. Mo(NO3)6·6H2O and ZrCl4 were dissolved in dimethylformamide, and then 2-methylimidazolium was added to the solution. After stirring at room temperature for 10 min, the reaction mixture was kept at 160°C in an oven for 24 h. After washing with ethanol twice, the mass ratio of Mo-based MOF / ZrO2, Mo(NO3)6·6H2O, ZrCl4, dimethylformamide and 2-methylimidazolium was 400:180:130:3.

[0026] S2, drying the obtained Mo-based MOF / ZrO2 in an oven at 70°C for 12 h, and then calcining the obtained product at 700°C for 2 h in an argon / hydrogen atmosphere of 95% Ar, 5% H2 to obtain Mo-Zr / CNT;

[0027] S3, the obtained Mo-Zr / CNT and Ti(C,N) powder mixture was fully mixed, and wet mixed in a full planetary ball mill vial with stainless steel balls and ethanol as the medium for 15 h at a speed of 150 r / min, dried at 70 °C and passed through a 100 mesh sieve to obtain a mixed powder, the mass ratio of the Mo-based MOF / ZrO2 and Ti(C,N) powder mixture was 100:50;

[0028] S4. Place the obtained mixed powder in a vacuum hot pressing sintering furnace for sintering. The sintering temperature range is 1450°C, the heating rate from room temperature to 800°C is 10°C / min, and the heating rate from 800°C to the sintering temperature is 6.25°C / min. When the temperature reaches 900°C, start to apply biaxial pressure. When the temperature reaches the set maximum temperature, the pressure is simultaneously increased to 34MPa. After maintaining the temperature and pressure for 30 minutes, the sample is cooled in the furnace to obtain the finished product.

[0029] In this embodiment, a method for preparing a composite metal-ceramic material comprises the following steps:

[0030] (1) Weigh the above materials according to the components, put the Mo-Zr / CNT composite material and CoB powder into an omnidirectional planetary ball mill for wet mixing and ball milling for 15 h, the ball mill speed is 150 r / min, the mixing medium is 8 mm and 4 mm diameter stainless steel balls, the ball-to-material ratio is 15:1, and a crude product is obtained;

[0031] (2) The obtained crude product was placed in a vacuum drying oven for drying, then placed in a cylindrical graphite mold, and then placed in a vacuum hot pressing sintering furnace with a vacuum degree of 1×10 -2 Pa, first pre-pressing is carried out with a pressure of 7MPa, and then the temperature is gradually raised to 1450℃ for pressure sintering, wherein bidirectional pressure is applied in the set temperature range of 1000℃ until the pressure is raised to 34MPa in the insulation stage. After insulation and pressure maintenance for 30min, the finished product is obtained after cooling with the furnace.

[0032] Example 2

[0033] A composite metal ceramic material comprises a binder and a hard phase, wherein the binder is 12 parts of a Mo-Zr / CNT composite material and the hard phase is 85 parts of a CoB powder.

[0034] The preparation method of Mo-Zr / CNT composite material comprises the following steps:

[0035] S1. Mo(NO3)6·6H2O and ZrCl4 were dissolved in dimethylformamide, and then 2-methylimidazolium was added to the solution. After stirring at room temperature for 10 min, the reaction mixture was kept at 160°C in an oven for 24 h. After washing with ethanol twice, the mass ratio of Mo-based MOF / ZrO2, Mo(NO3)6·6H2O, ZrCl4, dimethylformamide and 2-methylimidazolium was 430:190:140:4.

[0036] S2, drying the obtained Mo-based MOF / ZrO2 in an oven at 70°C for 12 h, and then calcining the obtained product at 700°C for 2 h in an argon / hydrogen atmosphere of 95% Ar, 5% H2 to obtain Mo-Zr / CNT;

[0037] S3, the obtained Mo-Zr / CNT and Ti(C,N) powder mixture was fully mixed, and wet mixed in a full planetary ball mill vial with stainless steel balls and ethanol as the medium for 15 h at a speed of 150 r / min, dried at 70 °C and passed through a 100 mesh sieve to obtain a mixed powder, the mass ratio of the Mo-based MOF / ZrO2 and Ti(C,N) powder mixture was 150:70;

[0038] S4. Place the obtained mixed powder in a vacuum hot pressing sintering furnace for sintering. The sintering temperature range is 1550°C, the heating rate from room temperature to 800°C is 10°C / min, and the heating rate from 800°C to the sintering temperature is 6.25°C / min. When the temperature reaches 900°C, start to apply biaxial pressure. When the temperature reaches the set maximum temperature, the pressure is simultaneously increased to 34MPa. After maintaining the temperature and pressure for 30 minutes, the sample is cooled in the furnace to obtain the finished product.

[0039] In this embodiment, a method for preparing a composite metal-ceramic material comprises the following steps:

[0040] (1) Weigh the above materials according to the components, put the Mo-Zr / CNT composite material and CoB powder into an omnidirectional planetary ball mill for wet mixing and ball milling for 15 h, the ball mill speed is 150 r / min, the mixing medium is 8 mm and 4 mm diameter stainless steel balls, the ball-to-material ratio is 15:1, and a crude product is obtained;

[0041] (2) The obtained crude product was placed in a vacuum drying oven for drying, then placed in a cylindrical graphite mold, and then placed in a vacuum hot pressing sintering furnace with a vacuum degree of 1×10 -3 Pa, first pre-pressing is carried out with a pressure of 7MPa, and then the temperature is gradually raised to 1550℃ for pressure sintering, wherein bidirectional pressure is applied in the set temperature range of 1000℃ until the pressure is increased to 34MPa in the insulation stage. After insulation and pressure maintenance for 30min, the finished product is obtained after cooling with the furnace.

[0042] Example 3

[0043] A composite metal ceramic material comprises a binder and a hard phase, wherein the binder is 14 parts of a Mo-Zr / CNT composite material, and the hard phase is 90 parts of a CoB powder.

[0044] The preparation method of Mo-Zr / CNT composite material comprises the following steps:

[0045] S1. Mo(NO3)6·6H2O and ZrCl4 were dissolved in dimethylformamide, and then 2-methylimidazolium was added to the solution. After stirring at room temperature for 10 min, the reaction mixture was kept at 160°C in an oven for 24 h. After washing with ethanol twice, the mass ratio of Mo-based MOF / ZrO2, Mo(NO3)6·6H2O, ZrCl4, dimethylformamide and 2-methylimidazolium was 460:200:150:5.

[0046] S2, drying the obtained Mo-based MOF / ZrO2 in an oven at 70°C for 12 h, and then calcining the obtained product at 700°C for 2 h in an argon / hydrogen atmosphere of 95% Ar, 5% H2 to obtain Mo-Zr / CNT;

[0047] S3, the obtained Mo-Zr / CNT and Ti(C,N) powder mixture was fully mixed, and wet mixed in a full planetary ball mill vial with stainless steel balls and ethanol as the medium for 15 h at a speed of 150 r / min, dried at 70 ° C and passed through a 100 mesh sieve to obtain a mixed powder, the mass ratio of the Mo-based MOF / ZrO2 and Ti(C,N) powder mixture was 280:120;

[0048] S4. Place the obtained mixed powder in a vacuum hot pressing sintering furnace for sintering. The sintering temperature range is 1550°C, the heating rate from room temperature to 800°C is 10°C / min, and the heating rate from 800°C to the sintering temperature is 6.25°C / min. When the temperature reaches 900°C, start to apply biaxial pressure. When the temperature reaches the set maximum temperature, the pressure is simultaneously increased to 34MPa. After maintaining the temperature and pressure for 30 minutes, the sample is cooled in the furnace to obtain the finished product.

[0049] In this embodiment, a method for preparing a composite metal-ceramic material comprises the following steps:

[0050] (1) Weigh the above materials according to the components, put the Mo-Zr / CNT composite material and CoB powder into an omnidirectional planetary ball mill for wet mixing and ball milling for 15 h, the ball mill speed is 150 r / min, the mixing medium is 8 mm and 4 mm diameter stainless steel balls, the ball-to-material ratio is 15:1, and a crude product is obtained;

[0051] (2) The obtained crude product was placed in a vacuum drying oven for drying, then placed in a cylindrical graphite mold, and then placed in a vacuum hot pressing sintering furnace with a vacuum degree of 1×10 -3 pa, first pre-pressing is carried out with a pressure of 7MPa, and then the temperature is gradually raised to 1550℃ for pressure sintering, wherein bidirectional pressure is applied in the set temperature range of 1000℃ until the pressure is increased to 34MPa in the insulation stage. After insulation and pressure maintenance for 30min, the finished product is obtained after cooling with the furnace.

[0052] Example 4

[0053] A composite metal ceramic material comprises a binder and a hard phase, wherein the binder is 20 parts of a Mo-Zr / CNT composite material and the hard phase is 100 parts of CoB powder.

[0054] The preparation method of Mo-Zr / CNT composite material comprises the following steps:

[0055] S1. Mo(NO3)6·6H2O and ZrCl4 were dissolved in dimethylformamide, and then 2-methylimidazolium was added to the solution. After stirring at room temperature for 10 min, the reaction mixture was kept at 160°C in an oven for 24 h. After washing with ethanol twice, the mass ratio of Mo-based MOF / ZrO2, Mo(NO3)6·6H2O, ZrCl4, dimethylformamide and 2-methylimidazolium was 500:220:160:6;

[0056] S2, drying the obtained Mo-based MOF / ZrO2 in an oven at 70°C for 12 h, and then calcining the obtained product at 700°C for 2 h in an argon / hydrogen atmosphere of 95% Ar, 5% H2 to obtain Mo-Zr / CNT;

[0057] S3, the obtained Mo-Zr / CNT and Ti(C,N) powder mixture was fully mixed, and wet mixed in a full planetary ball mill vial with stainless steel balls and ethanol as the medium for 15 h at a speed of 150 r / min, dried at 70 ° C and passed through a 100 mesh sieve to obtain a mixed powder, the mass ratio of the Mo-based MOF / ZrO2 and Ti(C,N) powder mixture was 300:150;

[0058] S4. Place the obtained mixed powder in a vacuum hot pressing sintering furnace for sintering. The sintering temperature range is 1650°C. The heating rate from room temperature to 800°C is 10°C / min, and the heating rate from 800°C to the sintering temperature is 6.25°C / min. When the temperature reaches 900°C, start to apply biaxial pressure. When the temperature reaches the set maximum temperature, the pressure is simultaneously increased to 34MPa. After maintaining the temperature and pressure for 30 minutes, the sample is cooled in the furnace to obtain the finished product.

[0059] In this embodiment, a method for preparing a composite metal-ceramic material comprises the following steps:

[0060] (1) Weigh the above materials according to the components, put the Mo-Zr / CNT composite material and CoB powder into an omnidirectional planetary ball mill for wet mixing and ball milling for 15 h, the ball mill speed is 150 r / min, the mixing medium is 8 mm and 4 mm diameter stainless steel balls, the ball-to-material ratio is 15:1, and a crude product is obtained;

[0061] (2) The obtained crude product was placed in a vacuum drying oven for drying, then placed in a cylindrical graphite mold, and then placed in a vacuum hot pressing sintering furnace with a vacuum degree of 1×10 -3 Pa, first pre-pressing is carried out with a pressure of 7MPa, and then the temperature is gradually raised to 1650℃ for pressure sintering, wherein bidirectional pressure is applied in the set temperature range of 1000℃ until the pressure is raised to 34MPa in the insulation stage. After insulation and pressure maintenance for 30min, the finished product is obtained after cooling with the furnace.

[0062] Comparative Example

[0063] A composite metal ceramic material comprises a binder and a hard phase, wherein the binder is 20 parts of a Mo-Zr composite material and the hard phase is 100 parts of CoB powder.

[0064] In this embodiment, a method for preparing a composite metal-ceramic material comprises the following steps:

[0065] (1) Weigh the above materials according to the components, put the Mo-Zr composite material and CoB powder into an omnidirectional planetary ball mill for wet mixing and ball milling for 15 hours, the ball mill speed is 150 r / min, the mixing medium is 8 mm and 4 mm diameter stainless steel balls, the ball-to-material ratio is 15:1, and a crude product is obtained;

[0066] (2) The obtained crude product was placed in a vacuum drying oven for drying, then placed in a cylindrical graphite mold, and then placed in a vacuum hot pressing sintering furnace with a vacuum degree of 1×10 -3 Pa, first pre-pressing is carried out with a pressure of 7MPa, and then the temperature is gradually raised to 1650℃ for pressure sintering, wherein bidirectional pressure is applied in the set temperature range of 1000℃ until the pressure is raised to 34MPa in the insulation stage. After insulation and pressure maintenance for 30min, the finished product is obtained after cooling with the furnace.

[0067] The performance of the composite metal ceramic materials prepared in Examples 1-4 and the comparative example is tested, and the test results are shown in Table 1 below:

[0068] Vickers hardness Thermal conductivity (W / m·K) Example 1 523 12.1 Example 2 526 11.8 Example 3 536 12.3 Example 4 566 14.6 Comparative Example 486 9.2

[0069] As can be seen from Table 1 above, the Mo-Zr composite material synthesized by using carbon nanotubes to constrain Mo-Zr as a binder improves the Vickers hardness and thermal conductivity of the composite metal-ceramic material.

[0070] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0071] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A composite metal-ceramic material comprising a binder and a hard phase, characterized in that: The binder is 10-20 parts of Mo-Zr / CNT composite material, and the hard phase is 80-100 parts of CoB powder; The preparation method of the Mo-Zr / CNT composite material comprises the following steps: S1, Mo(NO3)6·6H2O and ZrCl4 were dissolved in dimethylformamide, and then 2-methylimidazolium was added to the solution. After stirring at room temperature for 10 min, the reaction mixture was kept at 160 ° C in an oven for 24 h, and washed twice with ethanol to obtain Mo-based MOF / ZrO2; S2, drying the obtained Mo-based MOF / ZrO2 in an oven at 70°C for 12 h, and then calcining the obtained product at 700°C for 2 h in an argon / hydrogen atmosphere of 95% Ar, 5% H2 to obtain Mo-Zr / CNT; S3, the obtained Mo-Zr / CNT and Ti(C,N) powder mixture was fully mixed, and wet mixed in a full planetary ball mill vial equipped with stainless steel balls and ethanol as a medium for 15 h at a speed of 150 r / min, dried at 70 °C and passed through a 100 mesh sieve to obtain a mixed powder; S4. Place the obtained mixed powder in a vacuum hot pressing sintering furnace for sintering. The sintering temperature range is 1450-1650°C. The heating rate from room temperature to 800°C is 10°C / min, and the heating rate from 800°C to the sintering temperature is 6.25°C / min. When the temperature reaches 900°C, start to apply biaxial pressure. When the temperature reaches the set maximum temperature, the pressure is simultaneously increased to 34MPa. After maintaining the temperature and pressure for 30 minutes, the sample is cooled in the furnace to obtain the finished product.

2. A composite metal-ceramic material according to claim 1, characterized in that: In the step S1, the mass ratio of Mo(NO3)6·6H2O, ZrCl4, dimethylformamide and 2-methylimidazolium is 400-500:180-220:130-160:3-6.

3. A composite metal-ceramic material according to claim 1, characterized in that: In the step S3, the mass ratio of the Mo-Zr / CNT and Ti(C,N) powder mixture is 100-300:50-150.

4. A method for preparing a composite metal-ceramic material according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) Weighing the materials according to the components, placing the Mo-Zr / CNT composite material and CoB powder in an omnidirectional planetary ball mill and wet-mixing and ball milling for 15 h, the ball mill speed is 150 r / min, the mixing medium is 8 mm and 4 mm diameter stainless steel balls, the ball-to-material ratio is 15:1, and a crude product is obtained; (2) The obtained crude product was placed in a vacuum drying oven for drying, then placed in a cylindrical graphite mold, and then placed in a vacuum hot pressing sintering furnace with a vacuum degree of 1×10 -2 Pa-1×10 -3 Pa, first pre-pressing is carried out with a pressure of 7MPa, and then the temperature is gradually raised to 1450℃-1650℃ for pressure sintering, wherein bidirectional pressure is applied in the temperature range from 1000℃ to the set temperature until the pressure is raised to 34MPa in the insulation stage. After insulation and pressure maintenance for 30min, the finished product is obtained by cooling with the furnace.

Citation Information

Patent Citations

  • Preparation method of hydrogenation catalyst

    CN103100394A

  • Galvanizing zinc corrosion resistant boride and method for preparing metal ceramic gradient coatings

    CN105296909A